Annual Reviewer Acknowledgement - Sharma, Dr.Manik Sharma (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2019)
The Editorial team of the journal would like to thank the reviewers for their work in refereeing manuscripts during 2019